Efficacy, effectiveness, and safety of integrase inhibitors in the treatment of HIV/AIDS in patients with tuberculosis: systematic review and meta-analysis (Research, Society and Development, 2022)
Integrase Inhibitors are a promising new class of antiretroviral.  However, studies of these drugs in tuberculosis (TB) and, HIV/aids coinfection are scarce. Therefore, the aim of this review was evaluate the efficacy, effectiveness, and safety of integrase inhibitors in the treatment of HIV/AIDS in patients coinfected with tuberculosis (TB). The searches were performed in the MEDLINE, EMBASE, LILACS, COCHRANE, Web of Science, Scopus, and CINAHL databases using the terms “HIV”, “AIDS”, “tuberculosis”, “raltegravir potassium”, “dolutegravir”, “elvitegravir”, “bictegravir”, “integrase inhibitor”, and their respective synonyms. Reports from three randomised clinical trials and a historical cohort were included. Patients coinfected with TB and HIV/AIDS showed a good response to TB treatment (cure or treatment completed), which was above 85% in all arms of the evaluated studies. As a primary outcome, the HIV viral load suppression rates at week 48 were greater than 60% in all arms. The therapies evaluated in patients coinfected with TB and HIV/AIDS were also within the limits of the included studies, there were no significant drug-related adverse events. However, there was no significant difference in the efficacy outcomes viral load suppression between the efavirenz and integrase inhibitor arms, and regarding safety outcomes, there were few events compared with the total. Integrase inhibitors in patients co-infected with TB and HIV/AIDS appear to be effective, well tolerated and constitute an alternative to efavirenz in clinical protocols. However, the use of this drug twice a day compromises adherence to treatment. The role of these drugs should be better determined by further good methodological quality studies to assess their long-term efficacy, effectiveness and safety.